Prospects of Increasing Tropical Rice Production Through Ratooning - Bahar, F.A.; De Datta, S.K. (Wiley, 1977)
Production of a rice (Oryza sativa L.) crop by ratooning is feasible under some conditions. Ratooning of rice eliminates two labor‐saving operations: raising seedlings in the seedbed and transplanting in the main field.Field experiments were conducted for 2 years on Maahas clay (an isothermic clayey mixed Aquic Tropudalf) to evaluate the performance of rice cultivars for ratooning ability and the agronomic practices that affect ratooning. The agronomic practices studied were cutting height of the crop produced from seed (referred to as the “main” crop), N level, plant spacing, water management, and degree of land preparation.All the cultivars that were grown as ratoon crops were infected by the grassy stunt virus disease; the same cultivars grown simultaneously by transplanting and direct seeding were not infected. That indicates the high risks of growing virus‐susceptible cultivars as a ratoon crop.